Kepemilikan Institusional Memoderasi Pengaruh Transaksi Hubungan Istimewa Terhadap Penghindaran Pajak - Etty Murwaningsari; Sistya Rachmawati (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
Aspects of sales, purchases, and related credit as well as taxation, especially tax avoidance and institutional ownership, are important information for the company’s stakeholders, so the relevant regulations are important. This research method was carried out by taking secondary data, namely manufacturing companies listed on the Indonesian stock exchange, the number of research samples was 50 manufacturing companies, according to purposive sampling criteria during the 2016-2020 period (5 years) so that the number of samples was 250 observations. Using regression moderating, the results show that relationship loan transactions, relationship purchasing transactions, and relationship sales transactions have no effect on tax evasion. Meanwhile, institutional ownership weakens the effect of relationship loan transactions and relationship sales on tax avoidance, while the effect of relationship purchasing transactions on tax avoidance is not moderated by institutional ownership.